1996
DOI: 10.1002/(sici)1098-2264(199612)17:4<245::aid-gcc6>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Allelic losses at loci on chromosome 10 are associated with metastasis and progression of human prostate cancer

Abstract: DNA samples from tumors and paired normal tissues from 48 patients with prostate cancer (stage B, 16 cases; stage C, 14 cases; stage D, 18 cases) were examined with 26 polymorphic markers spanning chromosome 10. Allelic losses were observed in 17 of the 46 cases (37%) that were informative with at least one of the markers. Detailed deletion mapping identified two distict commonly deleted regions on the long arm of chromosome 10 (10q22-q24:7 cM and 10q25.1:17 cM) and one on 10p, suggesting that at least three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…21 Both mammaglobin and lipophilin C (mammaglobin B) show considerable promise as markers for detecting micrometastatic cancer lesions in the lymph nodes and bone marrow. 23,24 The chromosomal proximity of the lipophilin C, mammaglobin, and uteroglobin genes strongly suggests that all three genes evolved by repeated duplications of a common precursor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Both mammaglobin and lipophilin C (mammaglobin B) show considerable promise as markers for detecting micrometastatic cancer lesions in the lymph nodes and bone marrow. 23,24 The chromosomal proximity of the lipophilin C, mammaglobin, and uteroglobin genes strongly suggests that all three genes evolved by repeated duplications of a common precursor.…”
Section: Resultsmentioning
confidence: 99%
“…Lipophilin B resides on chromosome 23, in a region of considerable interest. Not only does chromosome 10q22–23 harbor an anti‐oncogene strongly implicated in prostate cancer, 24 it has also been implicated in Cowden syndrome, an autosomal dominant hamartoma syndrome associated with a high risk of thyroid and breast cancer. 25,26 Although interest has justifiably centered on PTEN/MMAC1, evidence suggests that additional prostatic cancer tumor suppressor genes may be situated close to the PTEN/MMAC1 locus on 10q23.…”
Section: Resultsmentioning
confidence: 99%
“…Prostate cancer (PCa) is a leading cause of cancer deaths in Western countries and its incidence is also among the most rapidly increasing cancers in Japanese men. Many clinical, endocrinological, pathological, and genetic prognostic factors have been used for the management of PCa 1–6 . Understanding these factors will help to individualize PCa.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that PTEN/MMAC1 is involved in the metastasis process. In addition to the observation of 10q abnormalities and allelic loss in metastatic tumors (15, 17–20) Petersen et al . (21) recently showed that loss of heterozygosity on chromosome 10q is associated with the metastatic phenotype of squamous cell carcinomas of the lung.…”
mentioning
confidence: 99%